2018
DOI: 10.1111/apa.14221
|View full text |Cite
|
Sign up to set email alerts
|

Review shows that early foetal alcohol exposure may cause adverse effects even when the mother consumes low levels

Abstract: Even low levels of PAE can cause adverse foetal effects and not just in the brain. It is not currently possible to determine a safe period and level when alcohol consumption would not affect the foetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Similarly, Nelle et al [28] ( n = 33) also noticed a significant drop in heart rate (from 161 to 149 beats per min; p = 0.005) following RCBT [28]. Contrastingly Dani et al [29] ( n = 14) and Alkalay et al [30] ( n = 32) found no difference in heart rate following RBCT. However, it was subsequently demonstrated that heart rate correlates positively with the measured blood volume of preterm infants born at 24–32 weeks of gestation [31].…”
Section: Physiological Adaptive Response To Anaemia and Blood Transfumentioning
confidence: 95%
“…Similarly, Nelle et al [28] ( n = 33) also noticed a significant drop in heart rate (from 161 to 149 beats per min; p = 0.005) following RCBT [28]. Contrastingly Dani et al [29] ( n = 14) and Alkalay et al [30] ( n = 32) found no difference in heart rate following RBCT. However, it was subsequently demonstrated that heart rate correlates positively with the measured blood volume of preterm infants born at 24–32 weeks of gestation [31].…”
Section: Physiological Adaptive Response To Anaemia and Blood Transfumentioning
confidence: 95%
“…This was highlighted by a panel of young adults with FASD at the Seventh International FASD Conference (2017), who stated that rather than describing FASD as a brain‐based disorder, it should be described as a “whole‐body disorder” (Himmelreich et al., ). This conference also prompted publication of a minireview, highlighting that even low–moderate alcohol exposure can program chronic disease in offspring, at least from animal studies (Sarman, ).…”
mentioning
confidence: 99%
“…This review by Sarman provides paediatricians with new insights into the effects of prenatal alcohol exposure to help them communicate key messages about avoiding alcohol during pregnancy. The author looked at studies published since 2010, which showed that even low levels of prenatal alcohol exposure could cause adverse foetal effects on the brain and other organs . The review concluded that it is not currently possible to determine a safe period and level when alcohol consumption would not affect the foetus.
…”
Section: Even Low Levels Of Early Foetal Alcohol Exposure May Cause Amentioning
confidence: 99%